Directional hydrophone clusters reveal evasive responses of small cetaceans to disturbance at offshore windfarms ... - Graham, Isla; Gillespie, Douglas; Gkikopoulou, Kalliopi; Hastie, Gordon; Thompson, Paul (Dryad, 2022)
Mitigation measures to disperse marine mammals prior to pile-driving include acoustic deterrent devices and piling soft starts, but their efficacy remains uncertain. We developed a self-contained portable hydrophone cluster to detect small cetacean movements. Using an array of clusters within 10 km of foundation pile installations, we tested the hypothesis that harbour porpoises (Phocoena phocoena) respond to mitigation measures at offshore windfarm sites by moving away. During baseline periods, porpoise movements were evenly distributed in all directions. In contrast, animals showed significant directional movement away from sound sources during acoustic deterrent device use and piling soft starts. We demonstrate that porpoises respond to measures aimed to mitigate the most severe impacts of construction at offshore windfarms by swimming directly away from these sound sources. Portable directional hydrophone clusters now provide opportunities to characterise responses to disturbance sources across a broad ... : Harbour porpoise clicks and noise levels during mitigation activities and baseline periods were recorded using tetrahedral clusters of hydrophones connected to four-channel underwater acoustic recorders (SoundTrap ST4300HF, Ocean Instruments NZ) deployed on the seabed. Recordings on each hydrophone cluster were processed in open-source PAMGuard software to determine received noise levels and classify harbour porpoise clicks. Data on the timing of construction activities were provided by the windfarm developer (Moray Offshore Wind Farm (East) Ltd). ...